Analysis and Design of Web-Based ELC Parents Monitoring Application Information System Using Task Centered System Design Method - Yovita Dinni Kun Cahyo; Verri Kuswanto (ALGOR, 2022)
Monitoring is an activity in controlling activities that are mutually sustainable. In the worldof education, monitoring is one of the things that will be done to find out the academicdevelopment of a student. However, the monitoring that is usually carried out is informationcarried out between one and two people face-to-face or through short messages that havenot been computerized. It's the same with ELC courses that are still updating via shortmessages such as whatsapp. Therefore, we need an application that can be a mediumbetween parents and homeroom teachers. With this application, it is hoped that it can helphomerooms and teachers in conveying various information about students' academics. Andparents are facilitated with a real-time attendance system that can be seen in this applicationwhich was designed using the Task Centered System Design method. This method canprovide any recommendations that are needed by the user. Testing on this system is carriedout by direct interviews with the owner of the ELC as well as several employees who workat ELC who will use this application. Based on this test, the ELC Parents application cancarry out its orders in inputting student attendance and computerized student assessments.